Development Communication in Empowering Digital Santri Preneurs for Creative Economy at Asshidiqiyah - Ghanistyana, Lathifa Prima; Rohmatunisa, Raden Nita; Fitriah, Afifah (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2025)
This study aims to analyze the development communication patterns at Asshiddiqiyah Islamic Boarding School in West Jakarta, identify strategies for strengthening santri’s digital literacy and entrepreneurship, and formulate an applicable development communication model based on digital santri. The research employed a qualitative approach with a case study method through in-depth interviews, participatory observation, and focus group discussions (FGDs), allowing for an in-depth exploration of communication practices and barriers to technological access within the pesantren environment. The findings reveal that development communication is participatory and dialogical, involving caregivers, administrators, and santri from program planning to implementation. Strategies for strengthening digital literacy were carried out through a project-based curriculum, entrepreneurship training, provision of shared facilities, and the creation of a competitive ecosystem. The novelty of this research lies in the design of a development communication model for digital santri in the form of an Integrated Communication Matrix, which integrates hierarchical structures, Islamic values, and the creative participation of santri. This model fills the gap in the literature on pesantren-based development communication in the digital era and offers practical solutions to enhance literacy, economic independence, and the competitiveness of santri, while also being replicable in other pesantren.